2016
DOI: 10.1016/j.sysconle.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Boundary feedback stabilization of Fisher’s equation

Abstract: The aim of this work is to design an explicit finite dimensional boundary feedback controller for locally exponentially stabilizing the equilibrium solutions to Fisher's equation in both L 2 (0, 1) and H 1 (0, 1). The feedback controller is expressed in terms of the eigenfunctions corresponding to unstable eigenvalues of the linearized equation. This stabilizing procedure is applicable for any level of instability, which extends the result of [2] for nonlinear parabolic equations. The effectiveness of the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…The above feedback is exactly the same as that given in [8] and [9], which was used to construct a continuous-time boundary feedback control.…”
Section: The Stabilization Of the Linearized Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…The above feedback is exactly the same as that given in [8] and [9], which was used to construct a continuous-time boundary feedback control.…”
Section: The Stabilization Of the Linearized Equationmentioning
confidence: 99%
“…al. applied this control to Fisher's equation in [9], and proved that it can locally stabilize this kind of semilinear parabolic equations. In last decade, a different approach to construct explicit boundary feedback controller to stabilize the 1-D linear and nonlinear parabolic equations, which is the so-called backstepping method, was developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature there are plenty of results concerning the stabilization of the deterministic Burgers equation, for example we refer to [15] and [13]. The last one provides a global stabilization result, with some consequences on the stabilizability of the stochastic version.…”
mentioning
confidence: 99%
“…Indeed, the feedback law, we propose here, requires full state knowledge. However, taking into account the numerical results in [15], where a similar feedback is proposed for the stabilization of the Fischer equation, we may expect that only the knowledge on a part of the domain is enough. In [15] it is shown that measurements are needed only on (a, 1) instead of the whole interval (0, 1), where a ≤ 0.25.…”
mentioning
confidence: 99%